Transforming Technological Literacy through Appropriate Technology Socialization for Junior High School Students - Nugroho, Agung; sutrisno, imam; Arfianto, Afif Zuhri; Subekti, Joko (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
The rapid progress of information and communication technology in the era of the Fourth Industrial Revolution demands that younger generations possess strong technological literacy to adapt effectively to ongoing digital transformation. This study aims to enhance students’ technological literacy at SMPN 1 Karangrejo through socialization and practical activities using appropriate technology (AT). The research adopts a participatory descriptive method involving 40 junior high school students. The activities consist of four stages: preliminary observation, interactive socialization, hands-on construction of appropriate technology tools, and evaluation. Quantitative results show an average technological literacy increase of 35.2% with a normalized gain score of 0.71, indicating high effectiveness. Qualitative findings reveal enhanced student motivation, creativity, collaboration, and environmental awareness. The study demonstrates that project-based AT learning effectively transforms students’ technological understanding and attitudes, making it replicable in other schools with local adjustments.